(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The article considers the issues of new field of scientific knowledge the science of service. The author analyses the views on the subject of its study, high lights the importance of this problem not only from a scientific point of view, but also from the perspective of the educational process in the profile "Service" and "Tourism" assumed the formation basic knowledge about the service. The author distinguishes understanding of service in the narrow and broad sense and proves his point of view, but also pays attention to the correlation of the concepts of service sectors.